Masalah kebijakan sistem pendidikan di Indonesia - Jamiar, Harning (Maliki Interdisciplinary Journal, 2024)
Education is an important process in order to increase intelligence, creativity or skills, morals and strengthen personality. Characteristics of an education system include having educational goals, fulfilling legal and formal aspects, having an operational concept, being created by the authorities, being able to be evaluated, and being systematic. However, it cannot be denied that there are also many problems that exist in the education system policy, such as the low quality of facilities and infrastructure, the low quality of teachers and unequal teaching staff, curriculum problems in Indonesia, and expensive education costs.